Characterization of thin-film adhesion and phonon lifetimes in Al/Si membranes by picosecond ultrasonics - Martin Grossmann; Martin Schubert; Chuan He; Delia Brick; Elke Scheer; Mike Hettich; Vitalyi Gusev; Thomas Dekorsy (New Journal of Physics, 2017)
We quantitatively study interfacial adhesion in a two-layer membrane system consisting of Al and Si with femtosecond time-resolved laser spectroscopy. High-frequency acoustic pulses in the sub-THz regime are utilized to characterize the membrane system. In order to explain the distinct features of the measured data, a spring model for the Al/Si interface is employed. We show that acoustic dissipation in this system needs to be included for accurate modeling of the interface adhesion over a broad frequency range. This modeling approach yields a spring constant of ${η }_{Al-Si}=17$ $kg\,{nm}^{-2}\,{{\rm{s}}}^{-2}$ , an acoustic phonon lifetime of ${τ }_{Al}=68$ ps at 240 GHz in polycrystalline Al and a frequency dependence of the lifetime in Si $\propto \,{ω }^{-1}$ in the frequency range from 50–800 GHz.